Large-scale public venues as medical emergency sites in disasters: lessons from COVID-19 and the use of Fangcang shelter hospitals in Wuhan, China - Jing Han; Dongping Fang; Shengjie Pan; Zaishang Li; Ting Yuan; Benran Jiang; Di Gan; Bai Sheng; Zhongmin Liu (BMJ Global Health)
Since the COVID-19 outbreak, Wuhan has adopted three methods of admitting patients for treatment: designated hospitals, newly built temporary hospitals and Fangcang shelter hospitals. It has been proven that converting large-scale public venues such as stadiums and exhibition centres into Fangcang shelter hospitals, which serve as hospitals for isolation, treatment and disease monitoring of patients with mild symptoms, is the most effective way to control virus transmission and reduce mortality. This paper presents some experiences learnt from treating COVID-19 in Wuhan, the first city to report the outbreak and which suffered from a shortage of emergency supplies, heavy workload among staff and a shortage of hospital beds during the early stages of the pandemic. The experiences include location, accessibility, spacious outdoor area, spacious indoor space, power supply, architectural layout design and partition isolation, ventilation, sewage, and problems in the construction and management of Fangcang shelter hospitals. During the COVID-19 pandemic, traditional approaches to disaster preparedness have demonstrated intrinsic problems, such as poor economic performance, inefficiency and lack of flexibility. Converting large-scale public venues into Fangcang shelter hospitals is an important means to rapidly improve the function of the city’s healthcare system during a pandemic. This valuable experience in Wuhan will help other countries in their battle against the current COVID-19 pandemic and will also contribute to disaster preparedness and mitigation in the future.